Diachronic Change in the Utilization of Ostrich Eggshell at the Late Paleolithic Shizitan Site, North China - Song, Yanhua; Cohen, David J.; Shi, Jinming (Frontiers in Earth Science, 2022)
Forty one ostrich eggshell (OES) artifacts excavated at five localities of the Late Paleolithic Shizitan site, on the North China Loess Plateau, allow the observation of diachronic changes in the utilization of ostrich eggs in the production and use of ornaments considered to be technologies of social signaling, beginning during the Last Glacial Maximum (LGM) and continuing through the Younger Dryas. Based on changes in dimensions, production techniques such as drilling, coloration through heat treatment or the application of ochre, and stringing techniques, OES pendant and bead use at Shizitan is divided into four phases. Phases 1-3 feature only completed ornaments, usually with heavy usewear. Only in Phase 4, during the Younger Dryas, are blanks and drilled preforms found that indicate local production. While Phase 1 features the use of larger pendants colored grey/black by burning, subsequent phases see beads replacing pendants, no heat coloration, and the use of ochre pigment. The switch to beads corresponds with the change to microblade technology at Shizitan 29. Phase 3 shows a trend toward larger relative surface display area and maturation of techniques to produce visual effects of roundedness and weightiness. Phase 4 local production shows technological developments that allowed drilling smaller apertures while also decreasing bead diameter, and increased standardization, implying changing display objectives (stringing beads together with a uniform appearance). The changes observed in the Shizitan diachronic dataset may relate to changing requirements in social signaling—part of the adaptations hunter-gatherer groups made to survive the challenges of climatic change from LGM through the Terminal Pleistocene in North China.